2021
DOI: 10.1177/20458940211046156
|View full text |Cite
|
Sign up to set email alerts
|

PKR deficiency alleviates pulmonary hypertension via inducing inflammasome adaptor ASC inactivation

Abstract: Pulmonary hypertension (PH) is a progressive fatal disease that currently has no specific therapeutic approaches. In this study, dsRNA-dependent protein kinase (PKR) was considered a candidate molecule in PH. We demonstrated that PKR is activated in the endothelium of experimental PH models. Deletion of PKR or treatment with the PKR activation inhibitor C16 inhibited the development of PH. To explore the mechanism of PKR in PH, we detected its downstream signaling and found that PKR knockout represses apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This may have been the consequence of decreased cleaved, active IL‐1β in the lung as active IL‐1β is a known promotor of monocyte/macrophage recruitment. 28 Furthermore, IL‐1β induces medial hypertrophy and vascular remodeling by promoting SMC proliferation 29 , 30 , 31 and fibrosis. 32 We, therefore, conclude that the hemodynamic and vascular morphometric improvement by PFD in PAH may be downstream of decreased IL‐1β production mediated by the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been the consequence of decreased cleaved, active IL‐1β in the lung as active IL‐1β is a known promotor of monocyte/macrophage recruitment. 28 Furthermore, IL‐1β induces medial hypertrophy and vascular remodeling by promoting SMC proliferation 29 , 30 , 31 and fibrosis. 32 We, therefore, conclude that the hemodynamic and vascular morphometric improvement by PFD in PAH may be downstream of decreased IL‐1β production mediated by the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…PKR has been shown to directly bind NLRP3, and loss of PKR inhibits release of IL-1β, IL-18, and HMGB1 ( 40 ). Recently, PKR was found to be activated in the pulmonary vessels of both monocrotaline-treated and Sugen-hypoxia treated rats ( 41 ). PKR inhibition prevented PH development in these models, and was found to block ASC activation and subsequent release of IL-1β and HMGB1 ( 41 ).…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…Recently, PKR was found to be activated in the pulmonary vessels of both monocrotaline-treated and Sugen-hypoxia treated rats ( 41 ). PKR inhibition prevented PH development in these models, and was found to block ASC activation and subsequent release of IL-1β and HMGB1 ( 41 ). Mechanistically, PKR was found to promote HMGB1 and cytokine release from endothelial cells, leading to proliferation of cocultured smooth muscle cells ( 41 ).…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 In our recent studies, PKR has been revealed to be a key target in promoting endothelial cell senescence and pulmonary hypertension (PH) mediated endothelial injury. 9 , 10 In normal physiological conditions, the endothelium is a crucial regulator of vascular physiology and produces several substances to protect the layer of arteries. However, injured endothelial cells become the initial contributor to promote the development of cardiovascular diseases in a pathological phenotype.…”
Section: Introductionmentioning
confidence: 99%